Perbincangan tentang Pendidikan Islam di Indonesia - Muhaimin, Muhaimin (ULUL ALBAB Jurnal Studi Islam, 2001)
The Indonesian people and government, which had inherited the dualistic education system, both the colonial education and Islamic educational systems, did not give priority to one of them, but they endeavored to integrate it to be "a national educational system". Delivering religious education systematically in public schools (the secular and colonial schools system) was the one to make them religious and cultural based schools system. Giving a help and guide to Madrasah and Pesantren enhances them in sharpening human life and in developing themselves to be integrated in a national educational system. The discourse of Islamic educational thought, as found in some Islamic education literatures, focused on four issues, i.e.: dichotomy of the perennial knowledge and the acquired knowledge, deriving the Islamization of knowledge issues (including education); quality of religious education in schools and universities, especially in operational dimensions; the development of Islamic education integratedly to build the integrity of human being; discovering the philosophical concepts of Islamic education and the figures ' thoughts of it from classical and medieval ages to modern period. Such phenomena will be able to empower the Islamic education as a discipline of science, which has a specific and systematic object as well as the methodology of study.